Pierre Robin sequence in association with tracheo-oesophageal fistula: a heterogenous birth defect - A. Yelikar, Nitin; Imran, Ayesha; Singh, Bajrang (International Journal of Contemporary Pediatrics, 2017)
Pierre Robin Sequence (PRS) is not a genetic syndrome. It consists of multiple defects that occur as a result of a single structural anomaly. A full term male baby with micrognathia, retrognathia, glossoptosis and cleft palate was brought at second day of life for respiratory difficulty and unswallowed saliva. After clinical examination and abdomen radiograph, it was found that he had trachea-esophageal fistula. The fistula was ligated and esophageal anastomosis was done. Gavage feeding was commenced from fifth post-operative day with no problems. Karyotyping came out to be normal for him. On day 40 of life he arrived with failure to thrive and noisy breathing. Infants with Pierre Robin sequence develop airway obstruction soon after birth. Persistence of upper airway obstruction, is associated with serious consequences. This can be avoided by clinical evaluation and polysomnography.